IMPLEMENTATION OF DIFFERENTIATE LEARNING TO IMPROVE STUDENT LEARNING OUTCOMES IN MATHEMATICS SUBJECT - I Gusti Agung Ngurah Trisna Jayantika; Kadek Yoga Santhika (Indonesian Journal of Educational Development (IJED), 2023)
Student’s learning outcomes were low in Mathematics. This study aimed to improve student’s learning outcomes with differentiated learning. Differentiated learning was used by differentiating the teaching approach to content and process. This research was a classroom action research which was divided into two cycles and began with pre-cycle. Each cycle consisted of planning, implementing, observing, and reflecting. The research subjects were 40 grade VIII-D student of SMP Negeri 8 Denpasar. This study used test and non-test instruments in the form of lesson observation sheets, interviews, and student’s learning outcomes tests. The results showed that in Cycle I the percentage of students who passed the minimum completeness criteria was 50% and then it increased in Cycle II to 77.5%, because it met the specified classical completeness, the research was stopped in Cycle II. Based on these results it could be concluded that there was an increase in student’s learning outcomes in Mathematics by applying the Differentiated Learning Approach.